A potential peril of pastoral care: Malpractice - Bernstein, Barton E. (Journal of religion and health, 1980)
The pastoral counselor may be a full-time counselor trained in pastoral care or a clergyman with a congregation, who from time to time serves his flock as a counselor, ministering to the personal needs of his congregation in a manner designated "pastoral care" or perhaps, more appropriately, "pastoral psychotherapy." Once a therapeutic relationship is established, a congregant acquires certain rights and the clergyman, duties. If these duties are breached due to the negligence of the pastoral counselor and this causes the congregant to be damaged in any way, the pastoral counselor may be liable and may be called upon to respond in damages. The cause of action is called malpractice. This paper isolates areas of actual and potential malpractice.